A Possible Case of COVID-19 Booster Vaccine–Associated Rhabdomyolysis and Acute Kidney Injury. (August 2022) - Unger, Kendra; Ponte, Charles D.; Anderson, Dylan
Background: Nearly 10 billion doses of the various messenger ribonucleic acid (mRNA) and viral vector vaccines against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) have been administered worldwide. Adverse drug reactions (ADRs) have been overwhelmingly mild to moderate in nature. Rare side effects have included myocarditis/pericarditis, thrombosis with thrombocytopenia syndrome (TTS), Guillain-Barré Syndrome (GBS), and death. However, vaccine-related ADR data are still being collected using a variety of reporting systems.Purpose: We will describe a case of suspected mRNA coronavirus disease 2019 (COVID-19) booster–related rhabdomyolysis in a woman who developed signs and symptoms 10 days after administration of the vaccine dose. With a Naranjo ADR probability score of 4, the vaccine was deemed to be a possible cause of our patient's rhabdomyolysis.Methods: A search of the VAERS (Vaccine Adverse Event Reporting System) mined in November 2021 revealed 386 reported cases of COVID-19 vaccine–related rhabdomyolysis. However, system limitations make the utility of the information problematic.Conclusions: It is vitally important that clinicians, scientists, and patients are aware of rhabdomyolysis as a potential side effect of vaccination. Suspected vaccine-related ADRs should be promptly and accurately reported via VAERS or other surveillance systems to support the ongoing effort to ensure vaccine safety.